Case Report: Clinical Features of a COVID-19 Patient With Cirrhosis - Zhou, Jian; Jiang, Dixuan; Wang, Wanchun; Huang, Kang; Zheng, Fang; Xie, Yuanlin; Zhou, Zhiguo; Sun, Jingjing (Frontiers in Medicine, 2021)
The coronavirus disease 2019 (COVID-19) was first reported in Wuhan, Hubei Province, China in December 2019. At present, COVID-19 has emerged as a global pandemic. The clinical features of this disease are not fully understood, especially the interaction of COVID-19 and pre-existing comorbidities and how these together further impair the immune system. Here, we report a COVID-19 patient with cirrhosis. A 73-year-old woman with cirrhosis reported a fever and cough on February 6, 2020. A chest CT indicated an infection in her bilateral lungs. She tested positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. The woman was treated with lopinavir and ritonavir tablets and interferon alpha-2b injection, but there was no obvious effect. Although this patient was basically asymptomatic after two days in the hospital, the inflammation of the bilateral lungs was slow to subside as shown in chest CT. In addition, the white cell count (WBC), absolute neutrophil count, and absolute lymphocyte count remained decreased, and the result of real-time reverse transcription polymerase chain reaction (rRT-PCR) assay was still positive for SARS-CoV-2 on hospital day 28. After infusion of plasma from a recovered COVID-19 patient four times, the patient tested negative for SARS-CoV-2. She was discharged on March 13, 2020. This patient tested negative for SARS-CoV-2 after infusion of plasma from a recovered COVID-19 patient four times. Cirrhosis could impair the homeostatic role of the liver in the systemic immune response, which may affect the removal of SARS-CoV-2. This could lead to a diminished therapeutic effect of COVID-19. Thus, clinicians should pay more attention to COVID-19 patients with cirrhosis.